TANTANGAN FARMAKOLOGI PENGGUNAAN STEROID TOPIKAL PADA PASIEN ORAL LICHEN PLANUS - Revi Nelonda; Nanan Nur’aeny; Irna Sufiawati (Faculty of Dentistry, Universitas Islam Sultan Agung, 2019)
Background: Oral lichen planus (OLP) is a chronic autoimmune disease sprinkled by T cells on the oral mucosal surface. The goal of OLP treatment is to eliminate erythema, ulceration and relieve symptoms. Corticosteroids are the first line in the treatment of OLP, either systemically or topically. The problem arises when using topical steroids, namely the time of topical steroid attachment to the oral mucosa, especially in cases of OLP with clinical desquamative gingivitis. Some studies suggest that the use of individual gingival tray can overcome this problem. Objective: To provide information on topical steroid use in OLP cases with desquamative gingivitis clinical signs.Case Management: Women, age 31, complain that pain with burning on the lips and mouth is aggravated by spicy food. Intraoral examination shows irregular white plaques on the buccal, labial and dorsal mucosa of the tongue accompanied by diffuse erythema in the anterior gingiva of the upper and lower jaws. Patients diagnosed with OLP. Lesions improve 3 months after topical steroid administration, except lesions on the gingiva. Gingival individual tray is then used to obtain adequate attachment of topical steroids on the gingiva surface. The gingiva showed significant improvement after a month later.Conclusion: The use of topical steroid concoctions applied to the gingival individual tray is effective in treating OLP lesions especially with clinical signs of desquamative gingivitis.